Reconstruction of msChi cDNA Contigs - Aiesah, Udin (Universiti Malaysia Sarawak, UNIMAS, 2010)
Chitinase is a glycosidae hydrolase enzyme that catalyzes the degradation of chitin and can be present in various organisms. Chitinase play an essential role in plant defence against fungal pathogens. Since chitinase have many diverse roles, further research should be done to understand the variability of function of this enzyme. The aim of this study is to join two overlapping cDNA fragments together. In this report, 3’ plasmid and 5’ plasmid of msChi were verified and amplified via PCR using primers emChi and T7 for 3’ contig and chi-sp2 and SP6 for 5’ contig. Then, the contigs were reconstructed via ligation treatment using T4 DNA Polymerase. The products then were amplified via PCR using primer T7 and SP6. A product of a size between 1kb-1.5 kb of full length msChi was generated successfully.